Multicenter epidemiological analysis of related factors in 10,808 hospitalized children with lower limb and pelvic fractures in China - Xin Qiu; Tianfeng Zhu; Hansheng Deng; Jianlin Chen; Haoran Feng; Zilong Huang; Jiahui Li; Xinyu Wang; Shizhe Liu; Shuaiyin Wang; Zhenkun Gu; Zhengyu Wu; et al. (Scientific Reports)
Abstract To analyze the causes, locations, associated injuries, and relevant factors of lower limb and pelvic fractures in hospitalized children in China to provide a theoretical basis for reducing the incidence of such fractures. A retrospective analysis of children with lower limb and pelvic fractures admitted to 27 tertiary children’s hospitals affiliated with China’s Futang Research Center of Pediatric Development between December 1, 2015, and December 31, 2019, was conducted. Inpatient cases were analyzed in the following age groups: Infants (< 2 years), Preschool children (2–5 years), School children (6–11 years), and Adolescents (12–18 years). This study included 10,808 pediatric patients (7152 males, 3656 females). The proportion of preschool children of lower limb and pelvic fractures was the highest. The 10,808 patients sustained a total of 14,398 fractures. The shafts of the femur, tibia, and fibula, the distal tibia, distal fibula, and the pelvis were the six most common locations. Of the 734 pelvic fractures in children and adolescents, the top three locations were the ilium, pubic bone, and the ischium. Of the total patients, 9599 underwent surgery, while 1209 received non-surgical treatment. The three most common causes of pediatric lower limb and pelvic fractures were falling over, traffic accidents, and falling from a height. Among the 1806 concomitant traumas, respiratory traumas was the most common, mainly pulmonary contusion. The most common concomitant traumas of nervous, digestive and urinary system were scalp hematoma, liver injury and kidney injury respectively. The analysis of the location, age, causes, and concomitant injuries of lower limb and pelvic fractures showed that the most common fracture requiring hospitalization was tibia fracture, which was most common in preschool children. The most common cause of injury in preschool children was traffic accident. In addition, children are susceptible to accidental injuries from multiple sources in life, which can cause serious consequences of multi-system injuries.